PERANCANGAN SISTEM INFORMASI MEDIA BELAJAR PADA SISWA SEKOLAH DASAR BERBASIS RFID - Sepsa Nur Rahman; Eva Rianti (Universitas Negeri Padang, 2017)
This study was conducted to make RFID applications as learning media information System in primary school students. This system is made by designing, making and implementing the components of the system which includes a microcontroller as process controllers, sound modules WTV as output which wil lgenerate. This system also uses RFID as input, where before the tool RFID function should be brought closer to the first RFID TAG and its output on the LCD. The results show a tool created to function properly and can be developed to a larger scale. Keywords : RFID, Sensors, Arduino, Sound Module ISD020